2008
DOI: 10.1002/jor.20697
|View full text |Cite
|
Sign up to set email alerts
|

Effects of changing strategies of fracture fixation on immunologic changes and systemic complications after multiple trauma: Damage control orthopedic surgery

Abstract: In the treatment of polytrauma patients, multiple studies have shown how the timing and the type of the initial surgery of long bone fractures influence the incidence of systemic complications. Database analyses documented that unduly long surgical procedures undertaken early after trauma increase the risk of acute respiratory distress syndrom (ARDS), especially when femoral shaft fractures are stabilized. Animal research and prospective clinical studies also support the fact that the type of stabilization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
12

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 109 publications
0
41
0
12
Order By: Relevance
“…Damage control orthopedics (DCO) is an approach that contains and stabilizes orthopedic injuries to enable improvement of the patient's overall physiology (21,27,28). Its purpose is to avoid worsening of the patient's condition by the ʻsecond hitʼ of a major orthopedic procedure and to delay definitive fracture repair until a time when the overall condition of the patient is optimized (28).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Damage control orthopedics (DCO) is an approach that contains and stabilizes orthopedic injuries to enable improvement of the patient's overall physiology (21,27,28). Its purpose is to avoid worsening of the patient's condition by the ʻsecond hitʼ of a major orthopedic procedure and to delay definitive fracture repair until a time when the overall condition of the patient is optimized (28).…”
Section: Discussionmentioning
confidence: 99%
“…Its purpose is to avoid worsening of the patient's condition by the ʻsecond hitʼ of a major orthopedic procedure and to delay definitive fracture repair until a time when the overall condition of the patient is optimized (28). DCO has been suggested for the management of femoral shaft fractures in severely injured patients because patients were unable to tolerate the burden of early determinative surgery (21,29). A clinical study investigated the type and timing of surgery and demonstrated that improvements in the clinical status coincided with a less sustained inflammatory response if DCO was followed (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Minimizing compressive stabilization will limit the risk of pressure sores and nerve injuries that have been reported with such devices. More definitive yet expeditious stabilization with external fixation of the pelvic fracture can be performed in the operating room [5,21,30,[32][33][34]. Concurrent resuscitation of the patient during fracture stabilization is critical.…”
Section: Initial Evaluation and Management Of The Pelvic Fracture Patmentioning
confidence: 99%
“…6 In the field of orthopedics, these concepts have been well understood for the management of long bone and pelvic fractures in polytraumatized patients. 7 In the case of isolated spinal fractures, the treatment regimen has been adequately defined and standardized; however, the optimum time, and the best type of fixation to use in unstable thoracolumbar fractures in polytraumatized patients, are still controversial. 8 At present, the management of unstable thoracic and lumbar fractures consists mainly of: 1) deferred fixation after the associated lesions have been resolved or 2) a more aggressive approach called "early total care" via invasive anterior approaches, corpectomy, and anterior fusion based more on purely mechanical aspects than on the physiopathology of the traumatized patient.…”
Section: Introductionmentioning
confidence: 99%